Characterization of microstructure and property evolution in advanced cladding and duct: Materials exposed to high dose and elevated temperature. Issue 9 (20th May 2015) - Allen, Todd R.; Kaoumi, Djamel; Wharry, Janelle P.; Jiao, Zhijie; Topbasi, Cem; Kohnert, Aaron; Barnard, Leland; Certain, Alicia; Field, Kevin G.; Was, Gary S.; Morgan, Dane L.; Motta, Arthur T.; et al.
Abstract: Abstract : Designing materials for performance in high-radiation fields can be accelerated through a carefully chosen combination of advanced multiscale modeling paired with appropriate experimental validation. The studies reported in this work, the combined efforts of six universities working together as the Consortium on Cladding and Structural Materials, use that approach to focus on improving the scientific basis for the response of ferritic–martensitic steels to irradiation. A combination of modern modeling techniques with controlled experimentation has specifically focused on improving the understanding of radiation-induced segregation, precipitate formation and growth under radiation, the stability of oxide nanoclusters, and the development of dislocation networks under radiation. Experimental studies use both model and commercial alloys, irradiated with both ion beams and neutrons. Transmission electron microscopy and atom probe are combined with both first-principles and rate theory approaches to advance the understanding of ferritic–martensitic steels.